Legislative Prospects For Climate Governance: Advocating A Specific Climate Change Law in Brunei Darussalam - Khairul Atiqah Binti Khairul Nurul Arsyad; Yusuf Ibrahim Arowosaiye (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Climate change refers to long-term alterations in global or regional climate patterns, particularly those that have become increasingly apparent due to anthropogenic activities such as fossil fuel combustion, deforestation, and unsustainable industrialization. Its severe environmental, social, and economic consequences have triggered international discourse and policy actions since the 1972 United Nations Conference is widely recognized as the First Earth Summit. In response, Brunei Darussalam has implemented a national climate change policy and several environmental regulations. However, a comparative analysis of jurisdictions with robust climate frameworks highlights a critical gap in Brunei’s legal response—namely, the absence of a specific, enforceable climate change law. This research investigates the adequacy of Brunei’s current policy instruments and evaluates the potential benefits of enacting a dedicated climate change statute. Utilizing a qualitative research design, the study analyzes international legal frameworks, especially the United Kingdom’s Climate Change Act 2008, and examines Brunei’s national policies and environmental legislation. The findings underscore the need for a targeted legal framework to strengthen governance, facilitate law enforcement, and ensure greater societal compliance. The study concludes with a call for legislative reform to complement existing policy instruments and support Brunei’s environmental commitments under global climate agreements.